Improve TCP performance in Ad Hoc netwoks - Zhou, Jianxin; Shi, Bingxin; Zou, Ling; Shen, Hui (Revista Colombiana de Computación, 2003)
Standard TCP misinterpret mobility loss in Ad hoc network as congestion loss, thus, it reduce the TCP performance by invoking unnecessary congestion control action. In this paper, we propose two approaches, simELFN (an variation of TCP-ELFN) and TCP-FSR (an variation of TCP-F). They can distinguish the essence of packet loss and avoid multiple consecutive dupACKs. Analyses and simulations show that they can achieve better TCP performance in Ad hoc network. Keywords: Ad hoc Networks; simELFN; TCP-FSR; TCP performance.